Data on the positive synergic action of dimethylacetamide and trehalose on quality of cryopreserved chicken sperm - Fabio Mosca; Manuela Madeddu; Ahmad Abdel Sayed; Luisa Zaniboni; Nicolaia Iaffaldano; Silvia Cerolini (Data in Brief, 2016)
This data article contains supporting information regarding the research article entitled “Combined effect of permeant and non-permeant cryoprotectants on the quality of frozen/thawed chicken sperm”(Mosca et. al., 2016) [1]. The combined effect of the permeant cryoprotectants agent dimethylacetamide and the non-permeant cryoprotectants agent trehalose on the quality of frozen-thawed chicken semen was assessed. In particular, the quantitative dimethylacetamide/trehalose ratio was investigated freezing semen samples according to the following treatments: trehalose 0.1 M+0% dimethylacetamide (DMA-0), trehalose 0.1 M+3% dimethylacetamide (DMA-3), trehalose 0.1 M+6% dimethylacetamide (DMA-6).